Internet of Things Architectures, Technologies, Applications, Challenges, and Future Directions for Enhanced Living Environments and Healthcare Systems: A Review - Marques, Gonçalo (2020)
Submitted by Nuno Garcia (nmgs@ubi.pt) on 2020-01-14T12:48:11Z No. of bitstreams: 1 2019 - Internet of Things Architectures, Technologies, Challenges, and Future Directions for Enhanced Living Environments and Healthcare Systems - A survey.pdf: 1889048 bytes, checksum: 8918e8f958e27bbb05138845fe20bdcd (MD5)